User Name Remember Me? Password

 Algebra Pre-Algebra and Basic Algebra Math Forum

 December 17th, 2018, 05:36 AM #1 Member   Joined: Aug 2016 From: Romania Posts: 30 Thanks: 1 x(0)=1 x(n+1)=2x(n)+1 S=x(0)+x(1)+...+x(n) S(2018)=? I know that the sequence from x(n+1) is 1,3,7,15,31. Now what do I do? How do I find x(n)? Last edited by skipjack; December 17th, 2018 at 10:10 AM. December 17th, 2018, 06:18 AM   #2
Math Team

Joined: Jul 2011
From: Texas

Posts: 3,005
Thanks: 1588

Quote:
 Originally Posted by alex77 x(0)=1 x(n+1)=2x(n)+1 S=x(0)+x(1)+...+x(n) S(2018 )=? I know that the sequence from x(n+1) is 1,3,7,15,31.Now what do I do?How do I find x(n)?
from observation, $x_n = 2^n-1$

$\displaystyle S_n = \sum_{k=0}^n (2^k - 1) = \sum_{k=0}^n 2^k - \sum_{k=0}^n 1 = \sum_{k=0}^n 2^k - n$

note $\displaystyle \sum_{k=0}^n 2^k = 2^0 + 2^1 + 2^2 + \, ... = 1+2+4+\, ...$
whose sequence of partial sums is $\{1,3,7,15, \, ... \} = x_n$

so, $\displaystyle S_n = \sum_{k=0}^n 2^k - n = x_n - n$

$S_{2018} = x_{2018} - 2018 = (2^{2018}-1) -2018 = 2^{2018} - 2019$ December 17th, 2018, 06:27 AM   #3
Member

Joined: Aug 2016
From: Romania

Posts: 30
Thanks: 1

Quote:
 Originally Posted by skeeter $S_{2018} = x_{2018} - 2018 = (2^{2018}-1) -2018 = 2^{2018} - 2019$
@skeeter The answer in my book was 2^2020-2021. December 17th, 2018, 06:46 AM   #4
Math Team

Joined: Jul 2011
From: Texas

Posts: 3,005
Thanks: 1588

Quote:
 Originally Posted by alex77 @skeeter The answer in my book was 2^2020-2021.
I'll have to go back over it and see if I can find an error ... December 17th, 2018, 07:14 AM #5 Math Team   Joined: Jul 2011 From: Texas Posts: 3,005 Thanks: 1588 Ok ... I messed up the exponent by starting the index with 1 instead of 0 $\{1,3,7,15,\, ... \} = 2^{n+1} - 1$ $\displaystyle S_n = \sum_{k=0}^n 2^{n+1} - 1 = \sum_{k=0}^n 2^{n+1} - \sum_{k=0}^n 1 = 2 \sum_{k=0}^n 2^k - (n+1) = 2(2^{n+1} - 1) - (n+1) = 2^{n+2} - 2 - n - 1 = 2^{n+2} - (n+3)$ $S_{2018} = 2^{2018+2} - (2018 + 3) = 2^{2020} - 2021$ Thanks from topsquark December 18th, 2018, 11:14 AM #6 Member   Joined: Aug 2016 From: Romania Posts: 30 Thanks: 1 @skeeter How does Sum(2^k, k = 0 .. n) =2^(n+1)-1? December 18th, 2018, 11:42 AM   #7
Math Team

Joined: Jul 2011
From: Texas

Posts: 3,005
Thanks: 1588

Quote:
 Originally Posted by alex77 @skeeter How does Sum(2^k, k = 0 .. n) =2^(n+1)-1?
$\displaystyle \sum_{k=0}^n 2^k = 2^0 + 2^1 + 2^2 + 2^3 + \, ... \, + 2^n$

note the partial sums ...

$\displaystyle \sum_{k=0}^0 2^k = 2^0 = 1 = 2^1 - 1$
$\displaystyle \sum_{k=0}^1 2^k = 2^0+2^1 = 3 = 2^2 - 1$
$\displaystyle \sum_{k=0}^2 2^k = 2^0+2^1+2^2 = 7 = 2^3 - 1$
$\displaystyle \sum_{k=0}^3 2^k =2^0+2^1+2^2+2^3 = 15 = 2^4 - 1$

...

$\displaystyle \sum_{k=0}^n 2^k = 2^{n+1} - 1$ December 18th, 2018, 12:02 PM #8 Global Moderator   Joined: Dec 2006 Posts: 20,942 Thanks: 2210 $\displaystyle \sum_{k=0}^n 2^k = 2\sum_{k=0}^n 2^k - \sum_{k=0}^n 2^k = \sum_{k=1}^{n+1} 2^k - \sum_{k=0}^n 2^k = 2^{n+1} - 1$ Thanks from topsquark December 18th, 2018, 01:14 PM   #9
Math Team

Joined: May 2013
From: The Astral plane

Posts: 2,258
Thanks: 929

Math Focus: Wibbly wobbly timey-wimey stuff.
Quote:
 Originally Posted by skipjack $\displaystyle \sum_{k=0}^n 2^k = 2\sum_{k=0}^n 2^k - \sum_{k=0}^n 2^k = \sum_{k=1}^{n+1} 2^k - \sum_{k=0}^n 2^k = 2^{n+1} - 1$
Nice. I was going to do an induction on it, but yours is much quicker.

-Dan Tags geometric, problem, progression Thread Tools Show Printable Version Email this Page Display Modes Linear Mode Switch to Hybrid Mode Switch to Threaded Mode Similar Threads Thread Thread Starter Forum Replies Last Post jiasyuen Algebra 1 May 14th, 2014 08:19 AM jiasyuen Algebra 1 May 1st, 2014 03:40 AM jiasyuen Algebra 7 March 23rd, 2014 08:29 PM jiasyuen Algebra 5 November 27th, 2013 05:47 AM jiasyuen Algebra 2 November 24th, 2013 07:31 AM

 Contact - Home - Forums - Cryptocurrency Forum - Top

Copyright © 2019 My Math Forum. All rights reserved.       